Long-term metabolic alterations in a febrile seizure model. (2nd April 2016) - Heng, Duanhe; Wang, Zhongcheng; Fan, Yuanteng; Li, Liang; Fang, Jian; Han, Song; Yin, Jun; Peng, Biwen; Liu, Wanhong; He, Xiaohua
Abstract : Objective: Febrile seizures (FS) are the most common neurological disease in infancy and early childhood, it can lead to metabolic changes and have long-term health implications. Aim of this study was to investigate the long-term effects of FS on metabolism. Methods: We measured certain metabolic parameters in hyperthermia-prone (HP) rats, which were developed using a selective breeding process and showed a lower seizure threshold than wild-type (WT) rats. Body weight, body length, abdominal circumference and the levels of fasting blood glucose, serum triglyceride, and total cholesterol concentrations were analyzed. The mRNA expression of genes involved in glucose and lipid metabolism was determined by qPCR and the histone methylation level in the liver was determined by western blot. Results: We found that the body weight of the HP rats was significantly lower than that of the WT rats. Similarly, the fasting blood glucose and serum triglyceride levels were lower in the HP group compared with the WT group. These changes were accompanied by increased mRNA expression of genes such as phosphoenolpyruvate carboxykinase (PEPCK) and carnitine palmitoyl transferase-1 (CPT-1), but not peroxisome proliferator-activated receptor α (PPARα). We also found tri-methylation of histone 3 at Lys9 and Lys27 was decreased in the HP group. Conclusions: These data may suggest an underlying mechanism by which FS have a long-term effect on energy metabolism via histone methylation.